THE ECONOMIC COMMUNITY OF PESANTREN AL-ITTIFAQ: OPPOSING MARKET CAPITALISM AND THE IMPROVEMENT OF COMPETITIVENESS - Fauroni, R. Lukman (IAIN Surakarta, 2019)
This study aims to elaborate on the solution the pesantren economic community takes in dealing with the penetration of market capitalism in the competitive era. This case study was conducted in Pesantren Al Ittifaq Bandung. Pesantren can successfully build a strong economic community through integrated education implementation including role modeling, facilitation, empowerment, and economic culturing in social capital-based communities. This article concluded that high consciousness of cooperation can improve competitiveness and be an appropriate strategy to oppose market capitalism penetration. The community?s capital asset leads to bargaining position and independence in partnership cooperation thereby can be beneficial and results in welfare. Keywords: pesantren, economic community, social capital, capital asset, cooperation, welfare